Future education: the benefits and challenges of integrating AI into the education world / Ja'izah Abdul Jabar and Wan Mardyatul Miza Wan Tahir - Abdul Jabar, Ja'izah; Wan Tahir, Wan Mardyatul Miza (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The rise of Artificial Intelligence (AI) has become a huge debate as its functions are expected to permeate into every aspect of our life. The history of AI dates to the hard science fiction of Isaac Asimov and Arthur C. Clarke in the second half of the nineteenth century, and it continued to be developed in the 1940s until it became a powerful man-made machine capable of thinking, learning, and making decisions on its own (Hassan, 2022). The evolution of AI involves a mixture of fantasies components, possibilities, demonstrations and promises which are finally designed as maps and navigations, facial identification, and recognition, chatbots, text editors and other popular examples of AI. Today, AI has become an integral part of our daily lives and has significantly impacted various industries, including education (Holmes, Bialek & Fadel, 2019).